MIGRASI BURUH MIGRAN PEREMPUAN (TKW): STUDI TENTANG MULTIPERAN DAN PEMBENTUKAN IDENTITAS ANAK - Desika Putri Mardiani; farida Istianah; Wiryo Nuryono; Lira Rifani Yuniar; Khoirun Nisa (LPPM Universitas Negeri Surabaya, 2025)
The migration of female migrant workers (TKW) has had complex implications for family structure, caregiving systems, and the identity of left-behind children. This study explores the dual role of TKW as both breadwinners and educators of their children, as well as its impact on children's identity formation. Using the Systematic Literature Review (SLR) method, this research analyzes previous studies on female migrant workers and long-distance caregiving strategies. The findings reveal that children from migrant families experience changes in intergenerational family relationships and face challenges in developing their social, cultural, and emotional identities. Although left-behind children exhibit higher resilience levels than those from non-migrant households, they often experience a caregiving deficit and a decline in psychological well-being. Additionally, gender-based caregiving patterns have undergone transformation due to mothers assuming the primary breadwinner role. This study highlights the importance of incorporating children's perspectives into migration policies and family welfare programs to create a more sustainable migration strategy. Keywords: Female Migrant Workers, Long-Distance Caregiving, Child Identity, Dual Roles, Transnational Families.